How Can Enemies Become Friends? Focusing on the “Gentiles” in the Gospels of the Bible - ZHANG, Yongchao (Journal of Research for Christianity in China (JRCC), 2025)
The Gospels of the Christian Bible, in stark contrast to the Old Testament's hostility and bloodshed toward “Gentiles,” gradually formed new commandments and a new “view of the Gentiles” under the Gospel of Jesus Christ's love. This holds profound implications for building “peace within the Asian community” today. First, identity is no longer confined by geography, race, or lineage but unified under new commandments and faith. Second, the commandments are renewed from the Old Testament law: love your neighbor as yourself and love your enemies. Third, human relationships center on the core relationship between humanity and God, making it possible for Gentiles to “turn enemies into friends.” The implicit challenge here lies in the fact that those who blaspheme against the Holy Spirit represent the fundamental boundary of this “view of the Gentiles.” Thus, “reverence for God” constitutes a necessary condition for building a peaceful community, while irreverence toward God remains a primary obstacle to constructing “peace within the Asian community” and even a “human peace community” in contemporary society.
Keywords: Foreign lands, turning foes into friends, divine love